KETIMPANGAN DISTRIBUSI TANAH DAN PENGARUHNYA TERHADAP KETAHANAN PANGAN - Sukamto, Iwan; Prianto, Yuwono (Faculty of Law, Universitas Pasundan, 2023)
The majority of land distribution in Indonesia is controlled by companies. Only 2.7 million hectares of the land are allocated for the community, while companies control the 94.8 percent of the land. The unequal distribution of land raises problems in the food security sector. This study examines the consistency of legal rules related to land distribution in the context of food security. For this reason, normative legal research is used based on secondary data collected which is analysed qualitatively using deductive logic. The policies on land distribution in supporting food security faced many obstacles and constraints because it is unable to accommodate strategic factors in the land sector, resulting in conflict of laws and regulations that have an impact on the slow distribution of agricultural land. Keywords: Agrarian Reform, Food Security, Inequality, Land Distribution.